Long non‐coding RNA FAL1 functions as a ceRNA to antagonize the effect of miR‐637 on the down‐regulation of AKT1 in Hirschsprung's disease. (30th July 2018) - Li, Yang; Zhou, Lingling; Lu, Changgui; Shen, Qiyang; Su, Yang; Zhi, Zhengke; Wu, Feng; Zhang, Hua; Wen, Zechao; Chen, Guanglin; Li, Hongxing; Xia, Yankai; et al.
Abstract: Objectives: Emerged evidence demonstrates that long non‐coding RNAs (lncRNAs) may play quintessential regulatory roles in the cellular processes, tumourigenesis and the development of disease. Though focally amplified lncRNA on chromosome 1 (FAL1) has been identified to have crucial functions in many diseases, its biological mechanism in the development of Hirschsprung's disease (HSCR) still remains unknown. Materials and methods: The expression levels of FAL1 in HSCR aganglionic tissues and matched normal specimens were detected by quantitative real‐time PCR (qRT‐PCR). Cell proliferation and migration were detected by Cell Counting Kit‐8 (CCK‐8) assay, Ethynyl‐deoxyuridine (EdU) assay and transwell assay relatively. Cell cycle and apoptosis were assessed using flow cytometer analysis. Moreover, the novel targets of FAL1 were confirmed with the help of bioinformatics analysis and dual‐luciferase reporter assay. Western blot assay as well as RNA immunoprecipitation (RIP) assay was conducted to investigate the potential mechanism. Results: FAL1 expression was markedly down‐regulated in HSCR aganglionic tissues and decreased FAL1 expression was associated with the diagnosis of HSCR. Cell functional analyses indicated that FAL1 overexpressing notably promoted cell proliferation and migration, while down‐regulation of FAL1 suppressed cell proliferation and migration. Additionally, Flow cytometry assay demonstrated that knockdown of FAL1 induced markedly cell cycle stalled in the G0/G1 phase. Furthermore, FAL1 could positively regulate AKT1 expression by competitively binding to miR‐637. Conclusions: These results illuminated that FAL1 may work as a ceRNA to modulate AKT1 expression via competitively binding to miR‐637 in HSCR, suggesting that it may be clinically valuable as a biomarker of HSCR.